Tecendo o matapi: uma arte de fazer no rio Campompema - CARDOSO, Maria Cristina dos Santos (2019)
This work will focus on a community of Matapi weavers in the Campompema River, taking as a parameter the cultural knowledge that is passed down from generation to generation, about its use in shrimp fishing. For this, there was my concern about knowing the meaning of weaving the Matapi to the groups and individuals of the community where I live, taking into account the imaginary that is expressed in this art. In this sense, the work aims to study Matapi and its constituent elements: the economic (income), social (ties), aesthetic (decorative) dimension. From the field researches, the importance of this craftsmanship to social, economic and cultural life was analyzed, as much of the artisans as of the fishermen and others who use it. We have seen that this type of handicraft is basically the only means of survival and is used as a symbol of social aggregation in the community.